ANALISIS PENYULUHAN PARTISIPATIF DALAM KEGIATAN PENYULUHAN PERTANIAN DI KABUPATEN KONAWE - Musadar Mappasomba; Salahuddin Salahuddin; Nurhayu Malik (Jurusan Penyuluhan Pertanian FP UHO, 2025)
The objective of this study was to analyze and describe participatory extension services in food crop agricultural extension services in Konawe Regency. The research was conducted from September to December of 2023. The research location was purposefully selected in Konawe Regency. The population under consideration consisted of all 113 agricultural extension workers (extension workers specializing in food crops) and civil servants (ASN) in Konawe Regency. The sample was selected through a census (saturated sampling). The present study employed descriptive statistical analysis, utilizing the class interval formula. The participatory extension services variables in this study are described in three categories: (1) low/insufficient; (2) moderate/sufficient; and (3) high/good. The findings suggest that the implementation of participatory extension services in Konawe Regency falls within the moderate category. Food crop extension workers in Konawe Regency have effectively implemented participatory extension indicators; however, improvements are necessary to achieve a high category.